Discovery of a new blind ground beetle in western French Pyrenees, and its relevance to the phylogeny of Pyrenean hypogean Trechini - Faille, Arnaud; Fresneda, Javier; Bourdeau, Charles (Zootaxa, 2013)
Geotrechus sarpedon sp. n., a new species of blind Trechini is described from Arbailles Massif, western Pyrenees, France. The generic attribution of the new species was challenging as it shares morphological features of both genera Geotrechus Jeannel, 1919 and Aphaenops subgenus Hydraphaenops Jeannel, 1926, confirming their polyphyly, which has been highlighted by previous molecular studies on the group. Molecular data suggests unambiguously strong affinities between the new species and the clade Aphaenops vasconicus Jeannel, 1913-A. galani Español, 1968 occurring in the same geographic area, and not related with Aphaenops ehlersi (Abeille de Perrin, 1872), type species of the subgenus Hydraphaenops. The species is included in the paraphyletic genus Geotrechus until its affinities with the other species of Geotrechus and A. (Hydraphaenops) are clarified.